Trends in Local Ecosystem Governance - Bork, Karrigan; Hirokawa, Keith (Frontiers in Climate, 2021)
The physical and biological factors that together determine ecosystem structure and function will be subject to enormous pressures under future climate regimes. These pressures will impact ecosystem processes and services, ranging from impacts on biodiversity to loss of essential ecosystem benefits to communities. Ecosystem management to maintain desired ecosystem conditions will become increasingly important. Existing governance structures are insufficient to provide the necessary guidance for these management efforts. The legal literature is increasingly focused on local ecosystem governance as a viable option to fill this governance gap. For example, increasing recognition of the value of ecosystem services to local communities has driven increased efforts to protect those services through local ecosystem initiatives. The local ecosystem governance scholarship is diffuse, making the literature difficult to access. Based on a review of the legal literature on local ecosystem governance over the last 20 years, this article marshals the theoretical arguments for and against local governance and to identify ongoing efforts to implement local ecosystem governance. The article also identifies both emerging challenges to local ecosystem governance and potential ways to address those challenges. From this critical review emerges actionable recommendations and critical research needs to improve local ecosystem governance.